التصوير البلاغي في القرآن الكريم بين الإمامين عبد القاهر الجرجاني والزمخشري : دراسة وموازنة - ندوة بنت حاج داود (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2006)
This study aims at examining the use 'taswir balaghi' (rhetorical representation) in the Qur’an in the light of the treatment of this phenomenon by 'Abd al-Qahir al-Jurjani and al-Zamakhshari. The researcher analyzes the similarities and the differences between the two scholars based on a comparative method that has been chosen for this study. In this respect, the theory of nazm (construction) which represents the cornerstone of alJurjani’s linguistic thought is discussed as well as al-Zamakhshari’s methodology of Qur’anic interpretation which was reconstructed from his exegesis, al-Kashshaf. Then, the researcher proceeds to an investigation of the relationship between the two in terms of the notion of ‘taswir balaghi’. It is found that there is a strong link between ‘taswir balaghi’ and the theory of construction and the notion of figurative representation such as personification, similitude and imaginative expression. The study then concludes that ‘taswir balaghi’ is one of the factors contributing to the superiority of Qur’anic expression and its embodiment of subtleties and implicit meanings. Both scholars are in agreement over this but they differ in explanations. Thus, al-Jurjani opines that rhetorical representation becomes evident through stylistic construction while al-Zamakhshari believes that it does so through tropes, similitudes and imaginative expressions.